The Role of Media in Setting the Migration Agenda : Comparative Insights from the 2022 Swedish Parliamentary Elections - Roztocil, Klaudia Marie; Votoupalová, Markéta; Blahušová, Anita; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
During the past years, Sweden, which has traditionally been known as a liberal and migrant-friendly society, has shifted towards a more restrictive stance in terms of migration. The trend, which had already begun in the aftermath of the 2015 refugee crisis, forcing Sweden to apply more stringent policies, has continued since. Migration, and especially its impact on security, took on a central role in the run-up to the most recent parliamentary elections in 2022. Overall, the elections represented another step further away from Sweden’s once-liberal stance on migration, with the inclusion of Swedish Democrats in the parliamentary cooperation and the establishment of the Tidö Agreement. Drawing from the concept of agenda-setting as the theoretical baseline, the main aim of the thesis was to examine how the migration agenda was set by the media during the period leading up to Sweden’s parliamentary elections. By employing content analysis as the methodological tool, a sample of articles published by various news outlets were analyzed in order to distinguish the themes occurring in them to find out the key narratives dominating the migration-related media discourse. Furthermore, the thesis takes a comparative approach by providing a comparison with the respective coverage in the Finnish media. In addition, the thesis aimed to explore the parallels between media coverage and the public’s opinion on political priorities in Sweden, highlighting the connection between the media and public agenda.
Vedoucí práce: Markéta Votoupalová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses